The Effect On Firms' Productivity Of Accessibility. The Spanish Manufacturing Sector - David Martín-Barroso; Juan A. Nú\~nez; Francisco J. Velázquez (European Regional Science Association (ERSA), 2013)
This paper evaluates the impact of accessibility on the productivity of Spanish manufacturing firms. We suggest the use of accessibility indicators to workers and commodities, integrating transport, land use, and individual components in their measurement, and computing real distances or travelling times using the Spanish full road network. The estimation is carried out in two steps. In the first one we estimate almost a hundred production functions using a panel of 155,937 firms along the 1999-2009 period from SABI database, applying Levinsohn and Petrin technique. From these estimations we derive the Total Factor Productivity function for year 2009, which is then explained in the second estimation step as a function of the accessibility indicators and additional control variables. Results evidence the crucial role of the accessibility to commodities, and a lesser but significant effect of workers? accessibility on firms? productivity.
Keywords: D24; R12; R40; 330